Factors That Influence The Occurrence of The Disease Tuberculosis in The Clinic of Tubercolosis - Oqui, Maximiano; Ximenes, Antonio; da Costa, Joaninha; Almeida Oqui, Serafino de; Evaristo Obeno, Olandino; Claudia da Costa Guterres, Ana; Jesus Amaral, Isabel de (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: Tuberculosis is a desease caused by mycobacterium tuberculosis, this desease transmitted by people who affect tuberculosis positive thtough the air. Mycobacterium tuberculosis invades the body’s respiratory tract and affects others organs through blood circulation. Objective: To know the factors that influence the occurrence of the disease tuberculosis in the  clinic of tubercolosis Klibur Domin Tibar, Liquisa Municipality, Timor-Leste in 2023. Method: The method used by the researcher is analytical quantitative with a Cross Sectinal approach. Sampling technique: The sampling technique that the researcher uses is non probability sampling with a total sampling approach. Instrument: The instrument that the researcher uses in this research is the questionnaire. Data analysis technique: Data analysis technique using spearman rank correlation formula, using spss formula, version 23.0. Result and Discussion: Based on the results of the pearson correlation analysis, the probability value of 0,5 is greater than the value of sig (1-tilled) 0,05> 0,000, this result show  that two variables are ralated. Conclusion: Based on result of te research the researcher concludes that; enviroment factors is retated with occurrence of tuberculosis disease, attitude factors is retated with occurrence of tuberculosis disease, nutritional factors is retated with occurrence of tuberculosis disease